Effect of C-terminal and N-terminal dimerization and alanine scan on antibacterial activity of the analogs of the peptide p-BthTX-I - Santos Filho, Norival Alves [UNESP] (2021)
Univ Estadual Paulista, Inst Quim, Dept Bioquim & Tecnol Quim, Sao Paulo, Brazil